Readability of Patient Education Materials in Physical Medicine and Rehabilitation (PM&R): A Comparative Cross‐Sectional Study. Issue 4 (18th September 2019) - Han, Alex; Carayannopoulos, Alexios G.
Abstract : Background: Patients are increasingly using the Internet to access health information. Patient awareness and education are crucial to advancing the field of PM&R, but many U.S. adults have insufficient health literacy skills to read and understand patient education materials (PEM), frequently written at the 10th‐15th‐grade level. Reading ability is key for health literacy, but no previous research has assessed the readability of PEM provided by professional PM&R societies. Objectives: Evaluate whether the readability of PM&R PEM meets the NIH‐recommended eighth‐grade reading level; compare readability of PM&R PEM to two commonly accessed patient resources for sports and rehabilitation medicine topics, handouts from the American Academy of Orthopaedic Surgeons (AAOS) and American Academy of Family Physicians (AAFP), whose readability has been previously analyzed. Design: Cross‐sectional study. Methods: Publicly accessible entries within the patient education section of websites sanctioned by professional PM&R societies, as well as the AAOS and AAFP, were analyzed for readability using two validated and widely used tools, the Flesch‐Kincaid Grade Level (FKGL) and Simplified Measure of Gobbledygook (SMOG) formulas. Comparative statistics were performed between the three surveyed specialties. Main Outcome Measures: FKGL and SMOG readability scores, which estimate U.S. grade level, or years of education, needed to comprehend text. Results: A total of 167 online PM&R resources were identified and compared to 94 articles from AAOS and 65 from AAFP. Mean SMOG and FKGL levels exceeded the eighth‐grade level for both PM&R (SMOG‐9.71, 95% CI 9.42‐10.0; FKGL‐10.35, 95% CI 9.99‐10.7) and AAOS (SMOG‐9.15, 95% CI 8.96‐9.35; FKGL‐9.51, 95% CI 9.29‐9.74), whereas AAFP met readability guidelines for both measures (SMOG‐7.00, 95% CI 6.74‐7.27; FKGL‐6.76, 95% CI 6.45‐7.07). SMOG and FKGL scores suggested significantly higher reading difficulty for PM&R compared to AAOS (SMOG P  = .017; FKGL P  = .0001) and AAFP (SMOG P  < .0001; FKGL P  < .0001). Results indicated that 17% of PM&R resources complied with NIH guidelines, vs 8% for AAOS and 83% for AAFP. Conclusions: The average readability of PM&R PEM exceeds the NIH‐recommended and average U.S. adult eighth‐grade reading level. The physiatry community can make its patient materials more comprehensible and accessible for patients by providing resources at a more appropriate reading level.